What lies beneath: microbial quality of rural groundwater explored by shotgun metagenomics - Manar-Aleslam M. Mattar; Walaa A. Eraqi; Mohamed Bakr Zaki; Akram M. Elkashlan; Khaled A. M. Abouzid; Ramy K. Aziz; Aymen S. Yassin; Ali H. A. Elbehery (Annals of Microbiology)
Abstract Background Groundwater is a vital freshwater resource, especially in rural areas; however, its microbial communities remain largely unexplored beyond traditional culture-dependent strategies. This study aimed to comprehensively analyze microbial communities in groundwater, with a focus on bacterial indicators of fecal pollution, pathogenic microorganisms, the antimicrobial resistome, virulence factors (VFs), and mobile genetic elements (MGEs). Nine groundwater samples comprising three replicates from three different hand pumps, representing different locations with different levels of contamination in Toukh, Qalyubia, Egypt, were analyzed by shotgun metagenomics. Results Taxonomic analysis identified Pseudomonadota as the dominant phylum across all pumps. Interestingly, species richness was significantly higher in pump 3 than in either pump 1 or 2. Besides, non-metric multidimensional scaling analysis showed distinct microbial community compositions across the three pumps. Bacterial indicators of fecal pollution, including Escherichia coli and Salmonella enterica, were highly abundant, alongside pathogenic microorganisms such as Pseudomonas aeruginosa in all pumps. VF genes, like hsiB1/vipA, associated with P. aeruginosa pathogenicity, were highly abundant in pumps 1 and 2. Antimicrobial resistance genes (ARGs), encoding resistance to aminoglycosides, beta-lactams, tetracyclines, and sulfonamides, were detected in all pumps. Among MGEs, insertion sequences were generally more abundant than plasmids and integrons, and several ARGs were genomically colocalized with MGEs, which suggests a strong potential for ARG mobilization by horizontal gene transfer. Conclusions These findings highlight the critical need for monitoring groundwater quality to mitigate antimicrobial resistance (AMR) and other health threats.